Analysis and management of credit risk in Algerian commercial banks: An attempt to develop a practical risk assessment model to improve banking performance - Omrani, Talal; Tahri, Seddik; Messaoudi, Rachida (The journal of contemporary issues in business and government, 2023)
The objective of this work is to propose a practical model, allowing decision makers responsible for granting bank loans within Algerian commercial banks, to determine the credit risks, their nature, weightings and levels, in order to be able to make the right decision on whether or not to grant a loan, and to avoid any losses to the bank. The proposed model can be applied to all debtors, based on the analysis of a number of financial and administrative variables, the financial situation and the guarantees offered.